Poster 197: Understanding the Biological Pathway of Progression of Hip OA Disease through Transcriptome Analysis. Issue 7 (30th July 2022) - Kamenaga, Tomoyuki; Haneda, Masahiko; Brophy, Robert; Nahal, Chadi; O'Keefe, Regis; Clohisy, John; Garrido, Cecilia Pascual
Objectives: Femoroacetabular impingement (FAI) has been established as an important etiologic factor for hip osteoarthritis (OA). Today, FAI is recognized as a leading cause of degenerative arthritis in the hip. An inflammatory cascade has been identified in cartilage samples from the impingement zone of the hip in patients undergoing surgical treatment for symptomatic FAI, suggesting that the impingement area is metabolically active and a potential structural precursor to hip OA. Moreover, it has been proposed that inflammation is observed at the impingement zone during early stage and extends to the rest of the joint during progression of disease. Still, the specific molecular and cellular mediating this pathogenic pathway of disease remains unknown. Investigating transcriptome-wide changes during disease progression is important for understanding osteoarthritis (OA) development. Hip FAI uniquely allows for studying hip OA during early disease stages. This study aimed to compare the transcriptome profile of articular cartilage in early-stage FAI to advanced OA secondary to FAI. Methods: Full-thickness cartilage samples were collected from the anterolateral head-neck junction (impingement zone) of 22 patients. 9 patients underwent hip preservation surgery for symptomatic cam FAI (early FAI) and 13 patients underwent total hip replacement for advanced OA secondary to cam FAI (late FAI-OA). RNA-sequencing was performed using Illumina HiSeq-3000 with single read extending 50 bases, targeting 30 M read per sample to probe a large, and the obtained data were analyzed for significant alterations in gene expression and KEGG pathways. Differential expression analysis was performed to determine differences between conditions and the results were filtered for genes with false-discovery rate (FDR) adjusted P values. Results: The early FAI group included younger subjects (mean=43.5 years) with lower Tönnis grade than the late FAI OA group (mean=59.6 years); however, there were no significant differences in sex, BMI, and α-angle between groups. In total, our data showed 52 genes transcripts differentially expressed between early FAI and late FAI OA (fold change -1.5 or 1.5, P-value <0.01), specifically 19 upregulated and 33 downregulated genes in early FAI when compared to late FAI-OA. Principal component analysis and heatmap revealed that patients were largely clustered into two distinct groups, indicating a distinct set of transcripts at different stage of disease (Fig. 1-A and B). Additionally, Volcano plot representing the trend of expression by adjusted log10 P value (y axes) and log2 fold change (x axes) at a fold change cut off > 2 log2 fold. (Fig. 1-C). Among genes showing different expression, two up-regulated genes: tachykinin precursor 1 (TAC1) and hypoxia inducible factor 3 subunit alpha (HIF3α), and three down-regulated genes: triggering receptor expressed on myeloid cells 1 (TREM1), pyruvate dehydrogenase kinase 1 (PDK1), and platelet derived growth factor subunit A (PDGFA), have been previously reported as associated with OA. The entire list of differentially expressed genes was found to be significantly associated with 42 canonical pathways, including 25 up-regulated and 17 down-regulated pathways in early FAI group (Figure-2). Several pathways: Peroxisome proliferator-activated receptor (PPAR) signaling pathway, Phosphatidylinositol-3-kinase/activate protein kinase (PI3K/Akt) signaling pathway, and Hypoxia-inducible factor 1 (HIF1) have been previously reported as associated with OA. Conclusions: This current study provides initial data regarding gene expressions in early and late stage of hip FAI disease. Most importantly, it suggests a distinct transcriptome profile of FAI (early stage) different from OA secondary to FAI (late stage). For gene expression analysis, up-regulated genes in early FAI includes TAC1 and HIF3α. In similar analysis using human knee OA, TAC1 expression was significantly upregulated in early stage of OA when compared to late stage. HIF3α expression is a feature of the human articular chondrocyte phenotype that is diminished in chondrogenic cells that express high levels of hypertrophic genes, such as OA chondrocytes. HIF3α is a regulator of chondrocyte hypertrophic terminal differentiation. TREM1, which is down regulated in early FAI, is increased in inflamed compared with normal areas of OA synovial membrane, suggesting a potential role of this glycoprotein in OA synovitis. In addition, TREM-1 knockdown exert anti-catabolic and anti-inflammatory effects on IL-1b-induced chondrocytes. These genes should be examined as a potential target to improve cartilage regeneration therapies in the near future. For pathway analysis, the most interesting finding of this study is that PPAR-ɤ is significantly up-regulated in early stage of disease when compared to late stage. PPAR-ɤ pathway is well known to be associated with OA progression. PPAR-ɤ suppression in human cartilage and aberrant epigenetic modification of OA susceptible genes contribute to OA development. Additionally, DNA methyltransferase (DNMT), which plays a significant role in regulating postnatal articular cartilage homeostasis, could be associated with PPAR-ɤ promoter methylation. Our findings support the expected hypothesis that PPAR-ɤ preservation by regulation of DNA methylation possessed therapeutic potential in treating OA. In conclusion, our observations suggest that the molecular mechanisms underlying the progression of OA secondary to hip FAI may have some unique and specific characteristics which have the potential to guide the development of tailored therapies specific to the hip joint.